Synthesis and Characterization of 1,3- Oxazepine and Benz [ 1,2-e][1,3] Oxazepine-4,7-Diones - Hussein, F.A.; Aa bid, 0. H.; Ali, K. F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
N- Benzylidene m-nitrobenzeneamines ( Schiff bases ) were prepared by condensation of m-nitroaniline with aromatic aldehydes . These Schiff bases were found to react with maleic anhydride to give 2-Aryl-3-( m-nitrophenyl )-2,3- dihydro ( 1,3] oxazepine -4,7-diones and with phthalic anhydride to give 2-Aryl-3-( m- nitrophenyl) -2,3 - dihydrobenz [ 1,2-e ) [ 1,3] oxazepine -4,7- diones whicb were reacted with pyrrolidine to give the anilide - pyrrolidides of maleic acid and phthalic acid.